Comparative Analysis of the MADS-Box Genes Revealed Their Potential Functions for Flower and Fruit Development in Longan (Dimocarpus longan) - Wang, Baiyu; Hu, Wenshun; Fang, Yaxue; Feng, Xiaoxi; Fang, Jingping; Zou, Tengyue; Zheng, Shaoquan; Ming, Ray; Zhang, Jisen (Frontiers in Plant Science, 2022)
Longan (Dimocarpus longan Lour.) is an important economic crop widely planted in tropical and subtropical regions, and flower and fruit development play decisive effects on the longan yield and fruit quality formation. MADS-box transcription factor family plays important roles for the flowering time, floral organ identity and fruit development in plants, however, there is no systematic information of MADS-box family in longan. In this study, 114 MADS-box genes were identified from the longan genome, phylogenetic analysis divided them into type I (Mα, Mβ, Mγ) and type II (MIKC*, MIKCC) groups, and MIKCC genes were further clustered into 12 subfamilies. Comparative genomic analysis of 12 representative plant species revealed the conservation of type II in Sapindaceae and analysis of cis-elements revealed that Dof transcription factors might directly regulate the MIKCC genes. An ABCDE model was proposed for longan based on the phylogenetic analysis and expression patterns of MADS-box genes. Transcriptome analysis revealed that MIKCC genes showed wide expression spectrums particularly in reproductive organs. From 35 days after KClO3 treatment, 11 MIKC genes were up-regulated, suggesting a crucial role in off-season flower induction, while DlFLC, DlSOC1, DlSVP and DlSVP-LIKE may act as the inhibitor. The gene expression patterns of longan fruit development indicated that DlSTK, DlSEP1/2 and DlMADS53 could be involved in fruit growth and ripening. This paper carried out the whole genome identification and analysis of longan MADS box family for the first time, which provides new insights for further understanding its function in flower and fruit.